The influence of consumption modes and consumers’ emotions on repurchase intention while considering the branded clothes - Muniza Syed,; Ayesha Khan,; Muhammad Abdullah Idrees,; Muhammad Arsalan Khan, (IJRDO - Journal of Business Management, 2020)
This study attempts to investigate the effect of consumption mode on consumer emotions and after that find out the impact of consumer emotions on repurchase intention. Find out the role of consumption and consumer emotions about branded products particularly for branded clothes. This study is based on the model which represent the relationship between dependent variables and independent variables and this model is supported by the theories, main theory of this study is Affect Balance Theory after that for understanding the consumers’ behavior the sample size of 250 was gather which was applied on SPSS and AMOS to run different test for getting the results. After the data collection data is used as pilot study and after that ready for main study and after that different statistical techniques were applied like CFA, EFA and SEM. The main test which is applied in this study was SEM which provides the hypothesis results and further these results will explain in discussion part. It is concluded that conspicuous consumption have significant impact on consumer pleasure but having insignificant impact on consumer guilt. In the same way style consumption have significant impact on consumer pleasure while insignificant impact on consumer guilt and after that pleasure and arousal have significance impact on repurchase intention but guilt have insignificant impact on repurchase intention. It is recommended that brand managers should add uniqueness in their brand and try to create the satisfaction in the mind of their consumer by their brand which will fulfill consumers’ intrinsic motivation and extrinsic motivation to buy branded products and will create the pleasure and arousal feelings which will leads to repurchase intention.